y=3+bx-2×2

Rewrite the equation as 3+bx-2×2=y.

3+bx-2×2=y

Subtract 3 from both sides of the equation.

bx-2×2=y-3

Add 2×2 to both sides of the equation.

bx=y-3+2×2

bx=y-3+2×2

Divide each term in bx=y-3+2×2 by x.

bxx=yx+-3x+2x2x

Cancel the common factor of x.

Cancel the common factor.

bxx=yx+-3x+2x2x

Divide b by 1.

b=yx+-3x+2x2x

b=yx+-3x+2x2x

Simplify each term.

Move the negative in front of the fraction.

b=yx-3x+2x2x

Cancel the common factor of x2 and x.

Factor x out of 2×2.

b=yx-3x+x(2x)x

Cancel the common factors.

Raise x to the power of 1.

b=yx-3x+x(2x)x1

Factor x out of x1.

b=yx-3x+x(2x)x⋅1

Cancel the common factor.

b=yx-3x+x(2x)x⋅1

Rewrite the expression.

b=yx-3x+2×1

Divide 2x by 1.

b=yx-3x+2x

b=yx-3x+2x

b=yx-3x+2x

b=yx-3x+2x

b=yx-3x+2x

Solve for b y=3+bx-2x^2